Interaction between Nursing Staff and Residents with Aphasia in Long-Term Care: A Mixed Method Case Study - Charlotta Saldert; Hannah Bartonek-Åhman; Steven Bloch (Nursing Research and Practice)
Introduction. Thousands of individuals with communication disorders live in long-term residential care. Nursing staff are often their primary communication partners. The positive effects of social interaction and person-centred care have been recognised but there remains a paucity of research on the content and quality of communicative interaction between long-term care staff and residents with aphasia. This mixed method study investigates the discourse in interaction between nursing staff and residents with aphasia. Methods. A routine care activity was explored in 26 video-recordings featuring four enrolled nurses and four elderly persons with severe aphasia. Factors such as goals and roles in the activity were mapped out and a qualitative discourse analysis was performed. Based on the findings a coding scheme was constructed and the amount of time spent in different interactional foci of discourse was explored. Results. From the qualitative findings three broad, but distinct, foci in the nurse-initiated interaction could be distinguished: (1) a focus on getting the task done with minimum interaction; (2) topics related to the task, but not necessary to get the task done; and (3) personal topics related to themes beyond the caring task. The analysis of distribution of time revealed that although most of the interaction was focused on the main care activity, between 3 and 17% of the time was spent in either task-related or non task-related interaction. The distribution varied between dyads and could not be related to the residents’ severity of aphasia nor the activity as such. Conclusions. An endeavour to interact socially with the residents with aphasia influences the nurses’ foci of interaction. Contextual and personal factors of the residents and nurses need to be considered in clinical work as well as research on how communication may be supported to facilitate social interaction and person-centredness in long-term care of people with aphasia.